Convenience stores: an obesogenic promoter in a metropolitan area of northern Mexico? - Ávila Arcos, Marco Antonio; Shamah Levy, Teresa; Del Monte Vega, Marti Yareli; Chávez Villasana, Adolfo; Ávila Curiel, Abelardo (Frontiers in Nutrition, 2024)
The prevalence of obesity in the Mexican school-age (5–11 years old) population increased from 8.9 to 18.1% between 1999 and 2022. Although overweight and obesity (OW + Ob) is a complex and multifactorial phenomenon, along with its increasing trend, changes in feeding patterns as a result of obesogenic environments that promote higher energy intake have been documented. The objective of the present work was to detect possible associations between schools and their proximity to and density of convenience stores in Monterrey, Mexico from to 2015-2018 period. Materials and methods: Anthropometric data were obtained from a subset of measurements of the National Registry of Weight and Height (RNPT) performed in the Monterrey Mexico metropolitan area in 2015 and 2018, and obesity prevalence was computed and classified into quintiles at the school level. Convenience store data were obtained from the National Directory of Economic Units (DNUE). The analyses consisted of densities inside 400-800m buffers, distance to the nearest stores, and cartographic visualization of the store’s kernel density versus OW + Ob hotspots for both periods. Results: A total of 175,804 children in 2015 and 175,964 in 2018 belonging to 1552 elementary schools were included in the study; during this period, OW + Ob prevalence increased from 38.7 to 39.3%, and a directly proportional relationship was found between the quintiles with the higher OW + Ob prevalence and the number of stores for both radii. Hotspots of OW + Ob ranged from 63 to 91 between 2015 and 2018, and it was visually confirmed that such spots were associated with areas with a higher density of convenience stores regardless of socioeconomic conditions. Conclusions: Although some relationships between the store’s proximity/density and OW + Ob could be found, more research is needed to gather evidence about this. However, due to the trends and problem magnitude, guidelines aimed at limiting or reducing the availability of junk-food and sweetened beverages at the school’s periphery must be done to control the obesogenic environment.